Baseball feet-first sliding technique - Hanson, T. M.; Hsieh, C. T. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this current study was to investigate the difference of planned and unplanned baseball feet-first sliding techniques. Five male collegiate baseball players (NCAA II) were recruited. Each subject performed 3 successful trials of regular running, planned, and unplanned baseball feet-first sliding techniques to the third base. 3D motion analysis was used to obtain kinematic data during the last 25 feet (7.62 m) of the performance before contacting the third base. Results showed planned sliding technique had significant longest time when compared to unplanned and regular running to the base (P < 0.01). Running to base had significant greater average horizontal velocity than both sliding techniques (P < 0.01). Additionally, unplanned sliding technique had greater average horizontal velocity than planned sliding technique (P < 0.01).